Sources of financing innovation - Nagy, Szabolcs; Pererva, P. G. (ФОП Томенко Ю. І., 2020)
It is proved that the experience of business angels in our country as a source of funding for innovation is not as developed as in the United States or Europe. This is due to the fact that Ukraine and Hungary do not have legislation protecting the rights of venture capital.
Keywords: financing; innovations; heuristics; intellectual property; heuristic postulates